The effectiveness of competitive activity of highly qualified basketball players is influenced by the indicators characterizing speed and strength qualities during jumps - Losin, B. E.; Grigorieva, D. V.; Minina, L. N.; Sergazinova, M. A. (Theory and Practice of Physical Culture, 2025)
Objective of the study. Within the framework of this study, the task was to establish the relationship between the speed of performing jumping movements and the success of competitive activity of professional basketball players.